CONTEMPORARY MATERIALS AND TECHNOLOGIES IN CIVIL ENGINEERING 2018 - Editorial, Foreword (Acta Polytechnica CTU Proceedings, 2019)
Date: June 13, 2018 Venue: Prague, Czech Republic URL: https://www.fsv.cvut.cz/konfer/nans2018.pdf Organized by: Department of Building Structures, Faculty of Civil Engineering, Czech Technical University in Prague Joint Laboratory of Technology Polymer Nanofiber of Institute of Physics of the Czech Academy of Sciences and Faculty of Civil Engineering at Czech Technical University in Prague Guest editors: Pavla Ryparová Zuzana Rácová Scientific comittee: Aleš Jíra Tomáš Plachý Josef Fládr Pavla Ryparová Václav Nežerka Local organizing comittee: Zuzana Rácová Kamil Staněk Guarantor of the peer review proces: Pavla Ryparová Guarantor of language editing: Pavla Ryparová